Ethnobotanical bioprospection of candidates for potential antimicrobial drugs from Brazilian plants: state of art and perspectives. - Benko-Iseppon, Ana Maria; Crovella, Sergio (Curr Protein Pept Sci, 2010)
Despite of the high biological diversity and traditional use of medicinal plants in Brazil, no comprehensive ethnobotanic review of plants with potential antimicrobial effects is available. In the present work own field information is aggregated with a literature review, identifying 433 Brazilian plant species potentially useful for identification of antimicrobial peptides. They included mainly woody species, distributed on 100 plant families (93 angiosperms and 7 pteridophytes) and 266 genera, covering all Brazilian regions and ecosystems. Main plant parts and indications for their use are presented and discussed, revealing the high potential that these plants present for the future planning strategies regarding the future development of antimicrobial drugs.
Keywords: Anti-Infective Agents; Biodiversity; Brazil; Ethnobotany; Plants